Wage risk and employment risk over the life cycle - Hamish Low; Costas Meghir; Luigi Pistaferri (Institute for the Study of Labor (IZA), 2008)
We specify a structural life-cycle model of consumption, labour supply and job mobility in an economy with search frictions that allows us to distinguish between different sources of risk and to estimate their effects. The sources of risk are shocks to productivity, job destruction, the process of job arrival when employed and unemployed and match level heterogeneity. Our model allows for four main social insurance programmes. In contrast to simpler models that attribute all income fluctuations to shocks, our framework allows us to disentangle the effects of the shocks from the responses to these shocks. Estimates of productivity risk, once we control for employment risk and for individual labour supply choices, are substantially lower than estimates that attribute all wage variation to productivity risk. Increases in productivity risk impose a considerable welfare loss on individuals and induce substantial precautionary saving. Increases in employment risk have large effects on output and, primarily through this channel, affect welfare. The welfare value of government programs such as food stamps which partially insure productivity risk is greater than the value of unemployment insurance which provides (partial) insurance against employment risk and no insurance against persistent shocks.
urn:nbn:de:101:1-20081014472
Keywords: D91; 330; Uncertainty; life-cycle models; unemployment; precautionary savings; Risiko; Arbeitslosigkeit; Einkommen; Arbeitsangebot; Lebensverlauf